Minimum amount of penicillin prophylaxis required to control Streptococcus pyogenes epidemic in closed community. Issue 6335 (10th July 1982) - Colling, A; Kerr, I; Maxted, W R; Widdowson, J P
Abstract : The prophylaxis required to control an epidemic of Streptococcus pyogenes throat infection in a junior detention centre has been reported. In a further epidemic an attempt was made to determine the minimum amount of penicillin required to control the outbreak. Oral penicillin (0.5 g) given as a single daily dose for 10 days to all boys after entry proved effective. The added risk of relatively deprived adolescent boys developing rheumatic fever is stressed.